Impact of Fatty Acid Types and Microwave Post-Treatment on the Physicochemical Properties of Water Caltrop Starch–Lipid Complexes - Pei-Chang Lee; Lih-Shiuh Lai (Foods)
This study investigates the effects of microwave post-treatment and fatty acid type on the physicochemical properties of starch–lipid complexes derived from water caltrop (Trapa taiwanensis Nakai) starch. Complexes were prepared using stearic acid (C18:0) or oleic acid (C18:1), followed by microwave post-treatment at varying durations. Morphological analysis revealed that the starch–stearic acid complex exhibited more plate-like structures and birefringent spots compared to the starch–oleic acid complex. The complexing index increased with extended microwave exposure, indicating enhanced complex formation. Fourier-transform infrared spectroscopy showed no significant variation in the 1047/1022 cm−1 absorption ratio, suggesting that the short-range molecular order remained unaffected. However, X-ray diffraction analysis indicated increased relative crystallinity, particularly in the stearic acid complex (10.4%) compared to the oleic acid complex (4.8%), likely due to the higher linearity and saturation of stearic acid. Differential scanning calorimetry confirmed the presence of both type I and type II crystallization in all samples. The starch–stearic acid complex exhibited greater thermal stability, promoted type II crystallization, and enhanced the ordered structure of type I crystallization. In contrast, microwave treatment had limited influence on the thermal properties of the starch–oleic acid complex. These findings demonstrate that microwave post-treatment facilitates starch–lipid complex formation and improves structural organization, particularly when saturated fatty acids are employed.